Sugar apple fairy tale. Volume 2 - Mikawa, Miri; Mikawa, Miri; Yozora no udon (Yen Press, 2023)
"Every autumn, the royal family sponsors a candy-crafting competition in the capital, and--following in her late mother's footsteps -- Anne's got her eyes on the prize. To that end, she sets off with her bodyguard and two companions in tow, but her plans go awry when the silver sugar she refined to present at the event suddenly goes missing..."--